Implementation of Unified English Braille by Teachers of Students with Visual Impairments in the United States. (November 2017) - Hong, Sunggye; Rosenblum, L. Penny; Campbell, Amy Frank
Introduction: This study analyzed survey responses from 141 teachers of students with visual impairments who shared their experiences about the implementation of Unified English Braille (UEB). Methods: Teachers of students with visual impairments in the United States completed an online survey during spring 2016. Results: Although most respondents knew if their state had a UEB transition plan, few participated in its development. Half attended workshops to learn about word-based UEB, but few attended workshops about math-based UEB. They believed their students would be successful in transitioning to word-based UEB but were less sure about their transition to math-based UEB. Discussion: The teachers believed they were more confident in their own skills and their students' future success with word-based UEB compared to math-based UEB. Additional clarification on the relationship between math-based UEB and the Nemeth Braille Code for Mathematics and Science Notation (hereafter, Nemeth code), an increased capacity of math-based UEB training, and clear instruction for high-stakes testing were considered to be urgent issues among these teachers. Implications for practitioners: Issues concerning the implementation of UEB in the United States will continue to challenge the field of visual impairment for the next several years. Although many teachers of visually impaired students had knowledge of word-based UEB and resources for its implementation, as of January 4, 2016, few were prepared to teach math-based UEB. As the United States is maintaining the Nemeth code, future studies, workshops, and the development of resources are needed to ensure braille users have the knowledge and materials they need in order to be literate in all aspects of UEB.